Kontribusi Tugas Siswa Terhadap Hasil Belajar Seni Tari Kelas VIII Di SMP N 2 Koto XI Tarusan Kabupaten Pesisir Selatan - Syelvi Juni Santika; Yuliasma Yuliasma (FBS Universitas Negeri Padang, 2019)
This article aims to find out how much the contributions of the students’ task toward dance art learning outcomes at class VIII in SMP N 2 Koto XI Tarusan Kabupaten Pesisir Selatan.This type of study was quantitative with a correlational method. The population in this study was all eighth grade students of SMP N 2 Koto XI Tarusan, while the sampling technique was carried out by the Cluster Sample technique where in this study the samples were taken which were 25 people. Data analysis was done by using product moment correlation using the correlation test.The result of the study shows that there is a contribution between coordination of students’ tasks towards dance art learning outcomes at class VIII in SMP N 2 Koto XI Tarusan Kabupaten Pesisir Selatan and a contribution of 18.5% is obtained. It is recommended for the teachers and students to pay attention to these factors.